Significance and prospect of interfaith dialogue exploratory study from the Qur’anic guidelines - Solihin, Sohirin Mohammad (s.n, 2012)
Muslim theology admits on variety of belief or faith followed by mankind. The existence of religious diversity is aimed, among other thing, at seeking common ground in disseminating goodness and eradicating evil practices in the community. The study attempts to reveal the guidelines on religious dialogue from the Qur’anic perspective as in many passages, Muslims' Scripture emphasizes on the importance of communication especially with people of the book.